Correction: Thermoreversible crystallization-driven aggregation of diblock copolymer nanoparticles in mineral oil - Derry, Matthew J. (Chem Sci, 2018)
Correction for ‘Thermoreversible crystallization-driven aggregation of diblock copolymer nanoparticles in mineral oil’ by Matthew J. Derry et al., Chem. Sci., 2018, 9, 4071–4082.